Facilitating the transition from hospital to home after hip fracture surgery: a qualitative study from the HIP HELPER trial - Welsh, A; Hanson, S; Pfeiffer, K; Khoury, R; Clark, A; Grant, K; Ashford, P; Hopewell, S; Logan, P; Crotty, M; Costa, M; Lamb, S; et al. (BioMed Central, 2024)
Background: People post-hip fracture have reported experiences of fragmented care and poor discharge planning, therefore improvements in patient flow are required. This study reports the challenges people face during the discharge process and offers potential solutions for improving the transition from hospital to home from the perspectives of patients, carers, and health professionals. Methods: This was a qualitative study embedded within a multi-centre, feasibility randomised controlled trial (HIP HELPER). We undertook semi-structured interviews with 10 patient-carer dyads (10 people with hip fracture; 10 unpaid carers) and eight health professionals (four physiotherapists, two occupational therapists, one nurse and one physiotherapy researcher) between November 2021 and March 2022. Data were analysed using the principles of Framework Analysis. Results: Participants identified challenges in the transition from hospital to home post-hip fracture surgery: ineffective communication, disjointed systems, untimely services and ‘it’s more than just the hip’. Possible solutions and insights to facilitate this transition included the need for reassurance, collaborative planning, and individualisation. Conclusion: The transition from hospital to home following hip fracture surgery can be a challenging experience for patients, and for friends and family who support them as carers, making them feel vulnerable, frustrated and uncertain. Enabling a coordinated, collaborative approach to discharge planning and early recovery provision is considered a positive approach to improving NHS care. Trial registration: ISRCTN13270387. Registered 29th October 2020.